Kelayakan Usaha Pengolahan Ikan Asin Dengan Mesin Pengering Sollar Cell : (Studi Kasus: Desa Tanjung Binga, Kecamatan Sijuk, Kabupaten Belitung) - Garist Sekar Tanjung; Raden Achmad Djazuli; Oki Wijaya (Universitas Djuanda, 2022)
Tanjung Binga is the largest salted fish producing area in Belitung Regency. The abundance of fish production in this area allows fishermen to produce various types of processed fish to extend the shelf life of their catch, especially for products exported outside the island. One of the mainstay processed products of fishermen is salted fish. However, currently the problem in processing salted fish occurs in the drying process which is still carried out in open spaces with traditional drying methods using sunlight. So that during the rainy season, the drying process can be hampered, which will affect the quality of the salted fish products produced. Therefore, this study aims to analyze the feasibility of processing salted fish using a portable solar cell dryer. The methodology used is to evaluate the financial feasibility and sensitivity analysis. The results showed that the salted fish product had the eligibility criteria with a PBP value of 0.48 years; NPV of Rp 3,268,039,778; B/C ratio of 1.37; and an IRR of 208.3% under normal conditions. In scenario 1, this effort is still considered in the feasible criteria. In scenario 2 (raw materials increase, total production decreases, interest rates increase), then the business is no longer feasible. Thus the salted fish processing business using a drying machine which is intended for fishermen and salted fish business actors deserves to be continued.